A THEMATIC STUDY OF PHILOSOPHY SCIENCE AND METHODOLOGY ON ESCHATOLOGY BASED ON THE AL-QUR’AN AND AL-HADITH TEXT - Muhammad Rizal Hidayat; Mohammad Izdiyan Muttaqin (Sekolah Tinggi Agama Islam Sadra, 2023)
Eschatology is the study of things that exist in life after death (akhirah). The law of studying eschatology is mandatory for every Muslim because its substance concerns the fifth pillar of faith, namely faith on judgment day. The concept and implementation of eschatology studies looked simply, but its impact is not small in daily life. Eschatology has lost its existence in modern science because the depth of its meaning has not been adequately revealed through research methodology. This research aims to explore the substance and meaning of eschatology through a philosophy of science and methodology. The common thread between this research and previous research is that eschatology still boils down to evidence that the judgment day and the resurrection day do exist, and Allah is the only God of the universe. The main sources for writing these thematic studies are the Al-Qur’an and Al-Hadith texts. The research method is a qualitative method. The interdisciplinary study of the philosophy of science and methodology involves aspects like axiology, ontology, and epistemology. The result is that the depth of eschatology meaning has been comprehensively revealed.